Bifurcations of a Two-Dimensional Discrete-Time Predrator-Prey Model - Hrustić, Sabina; Moranjkić, Samra; Nurkanović, Zehra (Sarajevo Journal of Mathematics, 2026)
In this paper, we study the dynamics and bifurcation of a two-dimensional discrete-time predator-prey model. The existence and local stability of the equilibrium points of the model are analyzed algebraically. It is shown that the model can undergo a transcritical bifurcation at equilibrium point on the $x$-axis and a Neimark-Sacker bifurcation in a small neighborhood of the unique positive equilibrium point. Some numerical simulations are presented to illustrate our theoretical results.